The Rate of Formation of Main Compounds in the Pyrolysis of Cinnamon Wood - Putri, Rahmi Eka; Kasim, Anwar; Emriadi, -; Asben, Alfi (International Journal on Advanced Science, Engineering and Information Technology, 2021)
Cinnamon wood has chemical and physical properties that can be optimized for use other than firewood. Lignocellulose compounds and a high density of raw materials would produce beneficial new compounds through pyrolysis. This research aims to make liquid smoke from cinnamon using pyrolysis and identify the concentration of the chemical compounds in liquid smoke and the rate of formation of the main compounds of liquid smoke. The Pyrolysis process was done twice, and the results were observed every 30 minutes. Chemical compounds of liquid smoke were analyzed using Gas Chromatography-Mass Spectroscopy (GC-MS). The crystal structure of charcoal produced from pyrolysis was analyzed using an X-ray diffractometer (XRD). The results showed that the liquid smoke, tar, charcoal, and the content lost after 150-minutes of pyrolysis was 28.94; 3.6; 42.92, and 24.54 %, respectively. Chromatography yielded ten peaks corresponding to compounds present in each stage of the process after 30 mins of pyrosis up to 150 mins. GC-MS analysis showed five chemical compounds, methanol, acetic acid, furfural, phenol, and guaiacol, as always present during the pyrolysis processes. Methanol, acetic acid, and phenol reached their highest concentration at the end of pyrolysis. The rate of formation of these compounds, particularly the methanol, continuously increased during the pyrolysis process. The length of the pyrolysis was proportional to the speed of methanol formation and the total yield.